Talking about transition : an exploration of the secondary to tertiary process for music students in a New Zealand context : a thesis submitted to Massey University and Victoria University of Wellington in fulfilment of the requirements for the degree of Master of Music in Musicology, Te Kōkī, New Zealand School of Music - Wenden, Lynne (Massey University, 2015)
There are complex challenges facing music students majoring in performance in New Zealand as they transition from secondary to tertiary study. As a result of their pretertiary experiences, these students form identities and develop subjectivities that are often discordant with notions of a broadly conceived degree-level education. Through exploring transition using ethnographic and interpretive approaches, it is clear that significant numbers of performance students are not engaging with the more theoretical aspects of their music degrees and can in fact be actively resistant to acquiring knowledge in areas of the curriculum that they perceive as falling outside those necessary to become a performer. This research suggests that education systems in secondary schools in New Zealand contribute considerably to these student subjectivities as despite individual levels of knowledge that students bring to their tertiary studies, these systems result in significant homogenous subjectivities and approaches. More generally, secondary schools appear unable to consistently prepare music students for their tertiary music studies for reasons that include curricula that is: widely interpreted, compartmentalised, heavily weighted towards assessments, and, in terms of performance assessments, lacking in validity. In ‘talking about transition’ within a New Zealand context, questions arise concerning pre-determined educational practices, which present unnecessary and prohibitive hurdles that can serve to culturally alienate our own students. For this reason and others, this research suggests these students will benefit from socio-culturally relevant pedagogical practice in addition to systems that provide accessible, manageable, and meaningful connections between secondary and tertiary levels of knowledge. Research findings also suggest that improved communication between education sectors and between institutions and students is key to empowering students with regard to their own learning.
Keywords: School music; Music; Instruction and study; Education, Higher; Tertiary education; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education::Music education